2016
DOI: 10.3892/ol.2016.5442
|View full text |Cite
|
Sign up to set email alerts
|

miR-506 suppresses neuroblastoma metastasis by targeting ROCK1

Abstract: Abstract. Neuroblastoma is a complex form of cancer with highly heterogeneous clinical behavior that arises during childhood from precursor cells of the sympathetic nervous system. In patients with neuroblastoma, mortality often occurs as a result of metastasis. The disease predominantly spreads to bone marrow, with a survival rate of ~40%. The current study demonstrates that microRNA (miR)-506 directly targets and downregulates Rho-associated, coiled-coil containing protein kinase 1 (ROCK1) in transforming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(30 reference statements)
0
19
0
1
Order By: Relevance
“…To further elaborate the relationship between NEAT1 and EMT, we investigated whether NEAT1 could act as a ceRNA. As a recognized EMT-associated molecule, miR-506 has been reported to be expressed in many types of cancer and to regulate EMT-associated genes, such as Snail2, Vimentin, and ETS-1 27 , 49 , 50 . Luciferase assays and Western blotting showed that NEAT1 might sponge miR-506 to promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To further elaborate the relationship between NEAT1 and EMT, we investigated whether NEAT1 could act as a ceRNA. As a recognized EMT-associated molecule, miR-506 has been reported to be expressed in many types of cancer and to regulate EMT-associated genes, such as Snail2, Vimentin, and ETS-1 27 , 49 , 50 . Luciferase assays and Western blotting showed that NEAT1 might sponge miR-506 to promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 NEAT1 is a bad prognostic factor and can regulate GC migration and invasion. 13 miR-506 can inhibit colorectal carcinoma progression by inhibiting LAMC1. miR-506 can inhibit neuroblastoma metastasis through repressing ROCK1.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cancer, miR-506 overexpression in HCT116-OxR cells enhances oxaliplatin sensitivity by inhibiting MDR1/P-gp expression via down-regulation of the Wnt/β-catenin pathway and thus provides a rationale for the development of miRNA-based strategies to reverse oxaliplatin resistance in colorectal cancer cells [ 3 ]. MiR-506 also suppresses neuroblastoma metastasis by targeting ROCK1 [ 4 ], and downregulation of miR-506 expression facilitates pancreatic cancer progression [ 5 ]. In osteosarcoma, downregulated miR-506 expression promotes osteosarcoma cell growth through JAG1 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%